Maternal knowledge and caregiver attitudes toward accurate complementary feeding according to WHO recommendations: A study at Riau, Indonesia (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2025)
The percentage of exclusive breastfeeding in Pekanbaru City in 2022 decreased compared to the previous year, thus putting babies at risk of receiving complementary foods too early, which has short-term and long-term impacts. Short-term negative impacts include babies losing nutrients from breast milk, triggering diarrhea, anemia, and reducing the baby's sucking ability. While long-term negative impacts include obesity, hypertension, allergies, and atherosclerosis. The purpose of this study was to determine the relationship between maternal knowledge and caregivers' attitudes towards providing complementary foods (MP-ASI) in the Payung Sekaki Community Health Center Work Area, Pekanbaru City, Riau. This study used a cross-sectional design, conducted from December 2023 to July 2024 in the Payung Sekaki Community Health Center Work Area, Pekanbaru City, Riau. The sample in this study were 163 mothers with babies aged 6-24 months with a sampling technique using purposive sampling. The instrument in this study was a questionnaire. The data analysis technique used univariate and bivariate analysis with Chi Square statistical test in SPSS 26. There was a relationship between maternal knowledge and caregiver attitudes towards providing complementary feeding in the Payung Sekaki Community Health Center Working Area with a p value = 0.000 (p <0.05). The better the mother's knowledge about complementary feeding, the more likely a mother will provide complementary feeding on time and respondents who have a positive attitude tend to provide complementary feeding on time.